A stability criterion for periodic solutions of two-dimensional discontinuous dynamical systems - Urmanchev, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish stability conditions for periodic solutions of two-dimensional systems of ordinary differential equations with pulse influence. We study the properties of the jump operator for such systems.